The computer record and analysis of struggle dynamics of the Judo fight - Kulasa, J.; Kalina, R. M. (The Engineering of sport 7, Volume 2, 2008)
The purpose of every sport rivalry is the result (in general victory). In the judo like in every sport fights, rivalry consist on direct wiping off two competitors. The result of that kind of fight is correlated with the level of training and in the same time with health, psychomotor competence and the tactical preparation. However, it is difficult to decide by using some analytical methods whether the competitor is able to win in a given and next fights. The winner is the one who, according to the principal judo rule, will use in an optimal way his brain together with the body. That is why according to some judo experts assessment the data from the competitors fights' observations might be more prognostic. The simplest analyses are the observations done by registering events using video, or writing the results down on the paper sheets and processing this Information e.g. by adding determined action. The modern approach provides necessity of analyzing some events during the fight (as well as record) in the function of time. The method of observation data registering together with using some Symbols which are a set of codes of given catches and throws in judo is a very time consuming and troublesome method in the sense of processing Information. Also laborious is method which the observation data are registered in a traditional way by using special sheets. The modern Computer technologies enable to register the data much faster and also they enable data's multifaceted processing. The pilot research shows that applying this innovative method is highly effective. The main aim of this work is the presentation of the method. Using this method goes beyond the formal of judo fights and might be applied in all kinds of sport fights and self-defense.